MAHAR DALAM PERSPEKTIF YUSUF AL-QARDHAWI DAN RELEVANSINYA TERHADAP PRAKTIK SOSIAL PERNIKAHAN DI INDONESIA - Makin, Makin; Hidayati, Tri Wahyu (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article explores the concept of marriage dower (mahar) through the lens of Yusuf al-Qordhawi’s thought and its relevance to contemporary practices in Indonesia. In Islamic tradition, mahar is an essential component of marriage contracts, encompassing legal, symbolic, moral, and socio-economic dimensions. Al-Qordhawi advocates for simplicity and affordability in mahar, emphasizing that it should not become a burden, but rather a source of blessings and commitment in marriage. In Indonesia, the practice of mahar is often shaped by cultural traditions and social pressure, leading to economic strain and reinforcing gender inequality. The emergence of unique and unconventional forms of mahar among young people reflects a symbolic resistance to materialistic interpretations. Using a qualitative, library-based approach, this study analyzes al-Qordhawi’s works and the social context in Indonesia. The findings suggest that al-Qordhawi’s wasathiy (moderate) approach offers a viable alternative for addressing contemporary marital issues by promoting justice, simplicity, and a spiritual reinterpretation of marriage values. His thought presents a framework for reforming Islamic family law in a way that is ethical, inclusive, and socially responsive to the needs of modern Indonesian society